2002
DOI: 10.1007/s005340200042
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intraoperative celiac plexus block with pharmacological therapy as a treatment for pain of unresectable pancreatic cancer

Abstract: Intraoperative celiac plexus block made pain control possible with reduced opioid consumption, representing an effective, safe, and simple tool for the treatment of pain caused by unresectable pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
(55 reference statements)
2
25
0
1
Order By: Relevance
“…Another randomized trial compared celiac block to medical pain management (non-steroidal anti-inflammatory drugs and opiates) and found a significant decrease in analgesic use (specifically opiates) in patients receiving chemical splanchnicectomy. 63 The mean age of this study was 67 years in the group receiving the block and 63 years in the pharmacologic group. In contrast, a similarly designed trial found no significant decrease in the use of opiates, no difference in quality of life, or difference in survival, although patients undergoing splanchnicectomy did score consistently lower on pain scores.…”
Section: Pain Managementmentioning
confidence: 96%
“…Another randomized trial compared celiac block to medical pain management (non-steroidal anti-inflammatory drugs and opiates) and found a significant decrease in analgesic use (specifically opiates) in patients receiving chemical splanchnicectomy. 63 The mean age of this study was 67 years in the group receiving the block and 63 years in the pharmacologic group. In contrast, a similarly designed trial found no significant decrease in the use of opiates, no difference in quality of life, or difference in survival, although patients undergoing splanchnicectomy did score consistently lower on pain scores.…”
Section: Pain Managementmentioning
confidence: 96%
“…While celiac plexus neurolysis is a currently accepted clinical treatment for severe intractable abdominal pain in abdominal malignancies and chronic pancreatitis, it is usually reserved for patients who have failed other treatment modalities. The reported year 1 success rate for pain relief is reportedly between 57-100%, depending on the approach and ethanol concentration (Okuyama et al, 2002;Vranken et al, 2002;Schmulewitz and Hawes, 2003;Klapman and Chang, 2005). Celiac plexus neurolysis requires surgical or anesthetic specialization and is usually performed at tertiary referral centers.…”
Section: Clinical Significancementioning
confidence: 99%
“…The reported first year success rate for pain relief is reported between 57 and 100%, based on the approach and ethanol concentration. [1][2][3][4] The effectiveness of blocks or sectioning of the sympathetic innervation, but not the vagus, indicates that afferent nerve fibers traveling with the sympathetic nerves are involved in transmitting nociceptive information from the pancreas. [5][6][7][8][9][10][11] Although generally well tolerated, reported complications after celiac plexus block include back pain, hypotension and diarrhea.…”
Section: Introductionmentioning
confidence: 99%